2000
DOI: 10.1002/1098-1136(200012)32:3<214::aid-glia20>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory ensheathing cells and Schwann cells differ in their in vitro interactions with astrocytes

Abstract: Transplanted olfactory ensheathing cells (OECs) are able to remyelinate demyelinated axons and support regrowth of transected axons after transplantation into the adult CNS. Transplanted Schwann cells (SCs) share these repair properties but have limitations imposed on their behavior by the presence of astrocytes (ACs). Because OECs exist alongside astrocytes in the olfactory bulb, we have hypothesized that they have advantages over SCs in transplant‐mediated CNS repair due to an increased ability to integrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
232
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(248 citation statements)
references
References 44 publications
12
232
4
Order By: Relevance
“…In a previous study, we reported that, after severe photochemical cord injury, OECs-transplanted rats showed significantly lower area of cystic cavity and lower expression of proteoglycan and glial fibrillary acidic protein (GFAP) by reactive astrocytes in comparison with nontransplanted animals (Verdú et al, 2001). In vitro studies also demonstrated that OECs modulate GFAP and proteoglycan expression in reactive astrocytes (Lakatos et al, 2000(Lakatos et al, , 2002. These results suggest that OECs create a favorable microenvironment at the lesion site that permits the regeneration of central axons.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In a previous study, we reported that, after severe photochemical cord injury, OECs-transplanted rats showed significantly lower area of cystic cavity and lower expression of proteoglycan and glial fibrillary acidic protein (GFAP) by reactive astrocytes in comparison with nontransplanted animals (Verdú et al, 2001). In vitro studies also demonstrated that OECs modulate GFAP and proteoglycan expression in reactive astrocytes (Lakatos et al, 2000(Lakatos et al, , 2002. These results suggest that OECs create a favorable microenvironment at the lesion site that permits the regeneration of central axons.…”
Section: Introductionmentioning
confidence: 81%
“…In the present study, we confirm these results at a longer time, 3 months postlesion, when the injury process has reached a steady state. Studies that have used cocultures with astrocytes showed that OECs did not induce overexpression of chondroitin sulfate proteoglycans (CSPGs) in astrocytes, whereas cocultured Schwann cells increased CSPG expression in astrocytes (Lakatos et al, 2000(Lakatos et al, , 2002. In vitro studies demonstrated that proteoglycan inhibits neurite outgrowth, and that a monoclonal antibody against proteoglycan neutralized this inhibitory activity (Bovolenta et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…OECs from neonatal rats were purified as previously described [20]. Briefly, the olfactory gentamicin (Sigma), and 5% FBS (Autogen Bioclear, Wiltshire, UK) on 13 µg/ml poly-Llysine-(PLL) (Sigma) coated 25cm2 flasks (Sigma).…”
Section: Cell Culture and Labellingmentioning
confidence: 99%
“…OECs secrete a host of growth factors, including vascular endothelial growth factor (VEGF), brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF), and nerve growth factor (NGF), all of which are important for neural, glial and endothelial cell function as demonstrated in a number of experimental studies [14][15][16][17][18][19]. Furthermore, compared to Schwann cells, OECs induce less astrocytic response in in vitro confrontation assays [20] as well as following transplantation into adult CNS white matter [21]. We have previously demonstrated the capacity of OECs to promote tissue remodelling, including axonal sparing and plasticity, neovascularization and remyelination after induced central axotomy [19], while a recent clinical report suggests that OECs combined with Schwann cell transplants can promote functional regeneration of supraspinal connections after spinal cord injury [22].…”
Section: Introductionmentioning
confidence: 99%
“…253 Both types of cells have been genetically modified prior to transplantation to deliver growth factors at the lesion site. 245,254,255 OECs have been reported to integrate more successfully with astrocytes, 256 and to induce less glial scarring 257 than SCs, but may themselves express inhibitory molecules (such as Nogo or proteoglycans, discussed in 'Stimulating axonal growth in the injured spinal cord' above) after transplantation. 258 Few experiments have directly compared SC-and OEC-transplantation in the same injury.…”
Section: Scs and Oecs: A Duel Or A Duet?mentioning
confidence: 99%